Histopathologic and functional effects of facial nerve following electrical stimulation - Sapmaz, Emrah; Kaygusuz, Irfan; Alpay, Hayrettin Cengiz; Akpolat, Nusret; Keles, Erol; Karlidag, Turgut; Yalcin, Sinasi (Springer, 2010)
The aim of the study is to investigate the functional and histopathologic changes in facial nerve due to the application of various violent and numerous electrical stimuli to the facial nerve. The study was carried out with Wistar rats weighing between 200 and 300 g. The facial nerves of the subjects were located and stimulated with electrical stimulator. Then five groups were created with 18 subjects in each group: Group 1, 1 milliampere (mA) electrical stimulus applied; Group 2, 2 mA electrical stimulus applied; Group 3, 3 mA electrical stimulus applied; Group 4, 4 mA electrical stimulus applied; Group 5, 5 mA electrical stimulus applied. All groups were divided into three sub-groups, each consisting of six subjects. The facial nerves of the subjects in first sub-group were stimulated 10 times, in second sub-group were stimulated 20 times and those in third sub-group were stimulated 30 times. The functions of the facial nerves were evaluated on first day, first week and first month, respectively. The facial nerves with branches were dissected from the surrounding tissues carefully. These specimens were investigated by light microscope about axonal degeneration, macrovacuolization and vascular congestion. Loss of facial functions was not observed in the subjects during follow-up process. There was no significant difference between groups regarding axonal degeneration, macrovacuolization and vascular congestion (P > 0.05). While less axonal degeneration was observed in group which was stimulated 10 times, more axonal degeneration was observed in groups which were stimulated 20 and 30 times (P < 0.05). The axonal degeneration, macrovacuolization and vascular congestion were observed more in 1-day groups (P < 0.05). Consequently, lesser violence and lesser number of electrical stimulus application to the facial nerve appears to be an important criterion for not damaging the facial nerve in patients in whom stimulators have been used.
Keywords: Facial nerve; Stimulator; Histopathology